The Influence Of Social Media Marketing And Brand Awareness On Purchasing Interest And Its Implications On Brand Loyalty (Study: Madame Gie By Gisella Anastasia) - Diana Astuti; Jerry Heikal (Sean Institute, 2024)
The purpose of this research was to determine and analyze the influence of social media marketing and brand awareness on purchasing interest and its implications for brand loyalty (Study: Madame Gie By Gisella Anastasia). This research discusses the dimensions contained in each variable which are then studied to determine the influence between the research variables and the object. The method used in this research is quantitative with a questionnaire survey via Google Form to 100 respondents using a random sampling method, then processed using Smart PLS. The results obtained from the hypothesis test (T test) are that social media marketing has a positive and significant relationship with purchase interest with a calculated t of 2.180 ≥ t table 1.984. Social media marketing does not have a positive and significant relationship with brand loyalty with a t count of 0.954 < t table 1.984. Brand awareness has a positive and significant relationship with purchase interest with a t count of 6.025≥ t table 1.984. Brand awareness does not have a positive and significant relationship with brand loyalty. Brand awareness has a significant effect on brand loyalty with a calculated t of 5.952≥ t table 1.98.4 Purchase interest has a positive and significant relationship with brand loyalty, the coefficient of determination in this study is 72%. The implications of this research can provide understanding for business actors to continue to pay attention to and build good social media marketing and brand awareness, especially Madame Gie.